Microsatellites for genetic studies and breeding programs in common bean Microssatélites para estudos genéticos e programas de melhoramento em feijoeiro - Tatiana de Campos; Luciana Lasry Benchimol; Sérgio Augusto Moraes Carbonell; Alisson Fernando Chioratto; Eduardo Fernandes Formighieri; Anete Pereira de Souza (Pesquisa Agropecuária Brasileira, 2007)
Twenty microsatelitte loci were identified and characterized in common bean. Microsatellites were tested in 14 genotypes. The allele number ranged from 1 to 3, and the polymorphism information content (PIC) was between 0.14 and 0.65. These polymorphic markers are available to be used for breeding programs. Vinte locos de marcadores microssatélites foram identificados e caracterizados em feijoeiro. Os microssatélites foram testados em 14 genótipos. O número de alelos variou entre 1 e 3, e o conteúdo informativo de polimorfismo (PIC) entre 0,14 e 0,65. Esses marcadores polimórficos estão disponíveis para serem usados em programas de melhoramento.